Body fat reference curves for children. - McCarthy, H; Cole, T; Fry, T; Jebb, SA; Prentice, A (2006)
OBJECTIVE: To refine the diagnosis of childhood obesity by creating new sex-specific centile curves for body fat and to base these references on a simple and affordable method that could be widely adopted in clinical practice and surveys. DESIGN: Body fat was measured by bio-impedance in 1985 Caucasian children aged 5-18 years from schools in Southern England. Smoothed centile charts were derived using the LMS method. RESULTS: The new body fat curves reflect the known differences in the development of adiposity between boys and girls. The curves are similar by sex until puberty but then diverge markedly, with males proportionately decreasing body fat and females continuing to gain. These sex differences are not revealed by existing curves based on body mass index. We present charts in which cutoffs to define regions of 'underfat', 'normal', 'overfat' and 'obese' are set at the 2nd, 85th and 95th centiles. These have been designed to yield similar proportions of overweight/overfat and obese children to the IOTF body mass index cutoffs. CONCLUSIONS: Direct assessment of adiposity, the component of overweight that leads to pathology, represents a significant advance over body mass index. Our new charts will be published by the Child Growth Foundation for clinical monitoring of body fat, along with the software to convert individual measurements to Z-scores.